Teacher Mindframes from an Educational Science Perspective - Klaus Zierer; Christina Lachner; Jonas Tögel; Denise Weckend (MDPI AG, 2018)
In this article, we describe the philosophical and the scientific background of teacher mindframes and we argue that educational professionalism consists not only of ability and knowledge (competence), but also of will and judgement (attitudes). To back up our argument, we present the results of our current research project on this matter.